THE MECHANISMS OF SECONDARY OVARIAN FAILURE AT OPERATIONS ON THE PELVIC ORGANS (EXPERIMENTAL STUDY) - I. A. Petrov; O. A. Tihonovskaja; I. I. Kuprijanova; A. O. Okorokov; S. V. Logvinov; M. S. Petrova; L. A. Agarkova (IRBIS LLC, 2016)
Objective - to establish a hysterectomy role in formation of secondary ovarian failure and to estimate possibility of application of DHEA. Materials and Methods. Sexually mature female rats outbred Wistar. Main group: 1a - hysterectomy + salpingectomy (n=24), Ib - hysterectomy (n=6), Ic - salpingectomy (n=6). Group of comparison - hysterectomy + salpingectomy + DHEA for 4 weeks after surgery (n=12). Intact control (n=12). Enzyme immunoassay serum concentrations anti-Müllerian hormone (AMH) and follicle stimulating (FSH) hormone, testosterone (T). Results. Shows statistically significant reductions AMH after operation at all time experience (2-10-30-40 days), increased FSH, only the end of the experiment (day 40), only the reduction of T by 10 day of the experiment compared to the control. Hysterectomy was not significantly altering the concentration of AMH, FSH and T on day 10. Salpingectomy significantly reduced the concentration of AMH and T, and has no effect on FSH. Use of DHEA 1 mg / day for 28 days did not alter the concentrations of FSH and T significantly increases AMH compared to animals after surgery, but still significantly lower than that in the control. Conclusion. Isolated hysterectomy does not substantially affect the functional ovarian reserve. Isolated salpingectomy, and also the combined operation volume (hysterectomy + salpingectomy) result in secondary ovarian failure. Effect of DHEA on the function of the gonads (AMH) remains uncertain.